2020
DOI: 10.1504/ijsem.2020.107793
|View full text |Cite
|
Sign up to set email alerts
|

The forefront of mobile shopping: an emerging economy's perspective

Abstract: The primary objective of this research is to identify the main factors affecting the intention to use mobile shopping in Malaysia. The theoretical base of this study was based on the mobile technology acceptance model (MTAM) as well as other theories such as diffusion of innovation (DOI). Data collection for this study spanned from May 2018 to September 2018. The survey was done via the distribution of questionnaires in selected local shopping malls. A total of 300 usable responses were collected for further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Their studies have noted the impact of social influences and perceived usefulness on NFC adoption. Extending on Tan's (2016) work, Hng, Foo, Lim, andNair (2020) found that reachability, which allows people to connect anytime and anywhere appear to influence customers' attitude towards the NFC payment.…”
Section: Mobile Payment and Nfc Technologymentioning
confidence: 91%
See 4 more Smart Citations
“…Their studies have noted the impact of social influences and perceived usefulness on NFC adoption. Extending on Tan's (2016) work, Hng, Foo, Lim, andNair (2020) found that reachability, which allows people to connect anytime and anywhere appear to influence customers' attitude towards the NFC payment.…”
Section: Mobile Payment and Nfc Technologymentioning
confidence: 91%
“…These items measure the extent to which the NFC technological infrastructure exists to support its usage. Perceived usefulness, perceived ease of use and intention to use were measured by items obtained from Davis et al (1989), Ooi and Tan (2016) and Hng et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations